Exploring the Coordination of Care for People with Multiple Morbidities and their Support Networks using Social Network Analysis: A Research Protocol - Lee, Mandy; Normand, Charles (My University, 2016)
Multimorbidity is the presence of two or more chronic conditions within one individual. Continuity of care and appropriate treatment decisions are essential for these individuals in order to avoid adverse outcomes and preventable healthcare costs. People with multimorbidity (_PMM_) can have multiple treatment options and/or require multiple services concurrently, which often is exasperated by fragmented health systems organised to deliver episodic care for single conditions (“disease silos”). Thus, achieving effective integrated care is a particularly complex task for this population. Yet research to date on how care is coordinated for PMMs has been limited, and extant research tend to focus on formal care delivery and seldom accounts for the “hidden” informal care provided by families and communities. There is a need for research that examines how access to care for this population is shaped by clinician-to-clinician and peer-to-peer interactions and how formal and informal care can be integrated.
16th International Conference on Integrated Care.
Keywords: Health service utilisation; Social network analysis; Service coordination; Multimorbidity; Integrated care; SOCIAL SUPPORT; Social Network Analysis; multimorbidity; Age-related disability; Chronic Health Condition; Mental Health/Psychosocial disability; Other; Community; Health; Relationships; Social services, interventions and supports